정관수술 수용자군과 비수용자군의 성기능 및 성만족도 비교 - 김동석 (연세대학교 보건대학원, 1988)
[한글] 정관수술은 수술의 간편성, 안전성 때문에 출생조절 목적으로 널리 이용되고 있다. 그러나 수술후의 성기능이나 성만족도에 대한 우려가 수술 수용자에게 가장 큰 의문점이었다. 따라서 정관수술 수용자의 성기능과 성만족도를 조사하는 것은 중요한 의미를 갖는다고 할 수 있다. 이 연구에서는 정관수술 수용자와 비수용자, 수술전과 후에 대한 성기능과 성만족도를 조사하기 위하여 예비군 598명을 대상으로 2단 집락추출법에 의하여 88년 3월 28일부터 88년 4월 11일까지 설문조사를 실시하였으며 조사의 결과는 다음과 같다. 1. 정관수술 수용자군의 성기능, 성만족도, 주평균 성교회수, 월평균 조조발기회수가 비수용자군보다 통계학적으로 유의하게 높았다. 2. 정관수술 수용자군의 수술후의 성기능, 성만족도, 주평균 성교회수는 수술전보다 통계학적으로 유의하게 높았으나 조조발기회수는 유의한 차이가 없었다. 3. 정관수술 비수용자의 피임실천별 성기능은 난관수술을 받은 군이 가장 높았고 루프와 콘돔, 피임약, 기타방법, 피임안함 순이었으며 통계학적으로 유의한 관련이 있었으나 성교회수 및 조조발기회수는 피임실천 종류에 따라 통계학적으로 유의하지 않았다 4. 정관수술 비수용자의 피임실천별 성만족도는 난관수술이 가장 높았으며 루프, 콘돔, 피임약, 기타방법, 피임안함 순이었으며 통계학적으로 유의하였다. 5. 성기능, 성만족간의 상관관계는 성기능과 성만족도가 가장 높았으며 ( f = 0.64 ), 성기능과 성교회수가 두번째 였으며 (r = 0.43 ), 성만족도와 성교회수, 성교회수와 조조발기회수, 성기능과 조조발기회수, 성만족도와 조조발기회수 순이었으며 통계학적으로 유의하였다. 이 연구의 결과를 종합하여 볼 때 정관수술 수용에 있어서 성기능과 성만족도에 관하여 우려할 바가 없으며 더 나아가 정관수술 수용이 성기능과 성만족도를 증진시킨다고 할 수 있다. [영문] Vasectomy is used as an ideal method of birth control in that it is simple and safe. However, worry concerning sexual function and sexual satisfaction after surgery is the most serious problem for the vasectomized. Therefore, investigation of sexual function arid sexual satisfaction in vasectomized men is of great importance. This study surveyed sexual function and sexual satisfaction in 598 men (reserve troops) including both vasectomized and nonvasectomized men, and more specifically examined sexual function and sexual satisfaction, before and after surgery. The survey was conducted by questionnaire from March 28, 1988 to April 11, 1988, according to the two stage sampling method. The results were as follows : 1. Sexual function, sexual satisfaction, the frequency of intercourse per week and the number of morning erections per month in the vasectomized men surpassed those of the nonvasectomized, and this was statistically significant. 2. Sexual function, sexual satisfaction, and the frequency of intercourse per week following surgery were statistically better than before surgery. But, the number of morning erections per month was not statistically significant. 3. The degree of sexual function among the nonvasectomized men who practiced contraceptive measures, was superior in the following order; of contraceptive measures: tubectomy, loop and condom(same degree), oral contraceptives, other methods, and non-contraception. This was statistically sifnificant. On the other hand, the frequency of intercourse per week and the number of morning erections per month in accordance with the type of contraceptive measures were not statistically significant. 4. The degree of sexual satisfaction for the nonvasectomized was superior in the order of tubectomy, loop, condom, oral contraceptives, other methods, and non-contraception. It was statistically significant. 5. Correlation between sexual function and sexual satisfaction was close, in the order of sexual function and sexual satisfaction (r=0.64), sexual function and frequency of intercourse (r=0.43), sexual satisfaction and frequency of intercourse, frequency of intercourse and morning erection, sexual satisfaction and morning erection. This was statistically significant. In conclusion, there is no need to worry about a decline in sexual function or a decrease in sexual satisfaction, as a result of a vasectomy. Rather, a vasectomy can contribute to an increase in sexual function and sexual satisfaction.
보건학과/석사